The Effect of Directly Observed Treatment Strategy on Cost Utility of Pulmonary Tuberculosis Patients at Banten Regional Public Hospital - Udin, Baha; Yusransyah, Yusransyah; Saepudin, Saepudin (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Pulmonary tuberculosis (TB) is one of the communicable diseases with high prevalence in some provinces in Indonesia, including the Province of Banten. Considering its high prevalence and the high cost of treatment resulting from multiple treatment components, research on the analysis of treatment costs of TB is very important. This study aimed to determine the effect of implementing the directly observed treatment (DOT) strategy on the cost-utility of pulmonary TB patients. The study was conducted at Banten Regional General Hospital using the perspective of the health provider and patients by involving 24 TB patients. Treatment cost was calculated by including direct medical costs, direct non-medical costs, and indirect costs, and then categorized into initial and final cost-utility. The average cost-effectiveness ratio (ACER) was then calculated by setting the patient's quality of life as the clinical outcome in this study. This study found that the average value of the average cost-utility ratio (ACUR) for the initial cost-utility and the final cost-utility were IDR 2,682,343.53 and IDR 2,402,153.15, respectively, and the difference was statistically significant (p=0.006). It indicates that the DOT strategy can potentially improve the utility costs of the treatment of TB patients at Banten Regional Hospital.